Structure formation in large-volume cosmological simulations of fuzzy dark matter: impact of the non-linear dynamics. Issue 2 (23rd June 2021) - May, Simon; Springel, Volker
ABSTRACT: An ultralight bosonic particle of mass around 10^-22 eV/c^2 is of special interest as a dark matter candidate, as it both has particle physics motivations, and may give rise to notable differences in the structures on highly non-linear scales due to the manifestation of quantum-physical wave effects on macroscopic scales, which could address a number of contentious small-scale tensions in the standard cosmological model, ΛCDM. Using a spectral technique, we here discuss simulations of such fuzzy dark matter (FDM), including the full non-linear wave dynamics, with a comparatively large dynamic range and for larger box sizes than considered previously. While the impact of suppressed small-scale power in the initial conditions associated with FDM has been studied before, the characteristic FDM dynamics are often neglected; in our simulations, we instead show the impact of the full non-linear dynamics on physical observables. We focus on the evolution of the matter power spectrum, give first results for the FDM halo mass function directly based on full FDM simulations, and discuss the computational challenges associated with the FDM equations. FDM shows a pronounced suppression of power on small scales relative to cold dark matter (CDM), which can be understood as a damping effect due to 'quantum pressure'. In certain regimes, however, the FDM power can exceed that of CDM, which may be interpreted as a reflection of order-unity density fluctuations occurring in FDM. In the halo mass function, FDM shows a significant abundance reduction below a characteristic mass scale only. This could in principle alleviate the need to invoke very strong feedback processes in small galaxies to reconcile ΛCDM with the observed galaxy luminosity function, but detailed studies that also include baryons will be needed to ultimately judge the viability of FDM.